PENGARUH PENAMBAHAN BERKAS BINTANG TERHADAP ANTENA MIKROSTRIP ARRAY 2X2 PATCH BINTANG PADA FREKUENSI ISM BAND 2,4 GHZ MENGGUNAKAN APLIKASI CST STUDIO SUITE 2018 - Kevin Icxaudy Hamonangan Sitinjak; Muhammad Fauzan Edy Purnomo (Jurnal Mahasiswa TEUB, 2022)
ISM band is a frequency band used for industrial, scientific, and medical needs. This ribbon is used without the need for a license. One of the devices that use this band is an antenna, the antenna serves to emit electromagnetic waves into free space. To get a wide coverage area, an antenna with a high gain is needed. Based on these needs, in this study it will be proposed to use the star patch method with a 2x2 array and the star file will be added. This star patch antenna will be used as an antenna that works at a frequency of 2.4 GHz. The 2x2 array method and the addition of a star beam are useful for increasing gain and improving the return loss and VSWR of the antenna. The test results show that the more elements and star beams, the higher the gain and the better the return loss and VSWR values.Keywords: antenna, array 2x2, star, ism, gain, return loss, vswr